Lenticular galaxies - the one in the middle - Malinga, Simon (Department of Astronomy, 2016)
The lenticular (S0) galaxies introduced by Hubble (1936) as a morphological transition class between elliptical and early-type spiral galaxies, which have the most massive bulges among disk galaxies, may have formed in several different ways as suggested by theoretical and numerical simulation studies. A sample of lenticular galaxies from the Spitzer Survey of Stellar Structure in Galaxies (S4G) using the Spitzer Space Telescope along with Sloan Digital Sky Survey (SDSS) was used for this project to study molecular gas properties as well morphologies associated with dust where molecular gas is present. A variety of image processing techniques are employed to study the details of galaxies to uncover the presence of molecular gas in S0 galaxies. We obtained colour maps using 3:6 and 4:5 micron images and SDSS r and i band images to find these galaxies have sufficient amount of dust and molecular gas along with variety of dust morphologies. In this thesis, we have shown, for the first time that the mass of molecular gas obtained by Carbon Monoxide (CO) is correlated to colour excess measured from (r - 3:6) and (i - 4:5) colour maps. It would be important to study this relation using advance facilities such as ALMA and MeerKAT to explore properties of molecular gas in nearby early-type galaxies in detail.